2014
DOI: 10.1093/mnras/stu453
|View full text |Cite
|
Sign up to set email alerts
|

Evolution in the bias of faint radio sources to z ∼ 2.2

Abstract: Quantifying how the baryonic matter traces the underlying dark matter distribution is key to both understanding galaxy formation and our ability to constrain the cosmological model. Using the cross-correlation function of radio and near-infrared galaxies, we present a largescale clustering analysis of radio galaxies to z ∼ 2.2. We measure the angular auto-correlation function of K s < 23.5 galaxies in the VIDEO-XMM3 field with photometric redshifts out to z = 4 using VIDEO and CFHTLS photometry in the near-inf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
43
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(51 citation statements)
references
References 62 publications
7
43
1
Order By: Relevance
“…Therefore we are likely tracing higher mass haloes with higher clustering amplitudes. The work by Lindsay et al (2014) is more similar to ours over the majority of angular scales, again with our two-point correlation function exhibiting an excess at small angles. For their work, Lindsay et al (2014) used sources from FIRST (Becker et al 1995, Helfand et al 2015, which have a flux density limit of 1 mJy at 1.4 GHz (∼ 5 mJy at 144 MHz) and so we expect our results to be similar to this.…”
Section: Clustering In the Xmm-lss Fieldsupporting
confidence: 84%
See 1 more Smart Citation
“…Therefore we are likely tracing higher mass haloes with higher clustering amplitudes. The work by Lindsay et al (2014) is more similar to ours over the majority of angular scales, again with our two-point correlation function exhibiting an excess at small angles. For their work, Lindsay et al (2014) used sources from FIRST (Becker et al 1995, Helfand et al 2015, which have a flux density limit of 1 mJy at 1.4 GHz (∼ 5 mJy at 144 MHz) and so we expect our results to be similar to this.…”
Section: Clustering In the Xmm-lss Fieldsupporting
confidence: 84%
“…This quantifies the excess probability of the clustering of galaxies at certain angular scales compared to a random distribution of galaxies in the same field (see e.g. Peebles Princeton University Press, 1980, Blake & Wall 2002, Lindsay et al 2014. To construct the random catalogue of galaxies, we considered the varying rms across the image as in Hale et al (2018).…”
Section: Clustering In the Xmm-lss Fieldmentioning
confidence: 99%
“…Repetition of this process allows the variance of the ω(θ) values to be estimated. Lindsay et al (2014) found Poisson errors were a factor of 1.5 to 2 smaller than those estimated with bootstrap. In this paper we use 100 bootstrap resamplings to estimate the uncertainty at the 16th and 84th percentiles of the resampling.…”
Section: Estimating ω(θ) Numericallymentioning
confidence: 62%
“…If the redshift is known precisely for each galaxy then this is unambiguous. In Lindsay et al (2014), for each redshift bin, the sum of the pdfs that have their peak in that bin is used e.g. there is some contribution from outside the bin.…”
Section: Projecting From 3d and Choice Of N (Z)mentioning
confidence: 99%
“…In their angular correlation analysis of the NVSS Overzier et al (2003) while the brighter, potentially FR II, sources had a scalelength r 0RR ∼ 14 h −1 Mpc. On the other hand clustering analyses of radio surveys matched to optical galaxies have found no luminosity dependence in the large-scale halo-halo regime (Donoso et al 2010;Fine et al 2011;Lindsay et al 2014b). Note that since the Overzier et al (2003) had no redshift information a considerable series of assumptions about the radio population were required to derive their result, on the other hand both Donoso et al (2010) and Fine et al (2011) Given the few constraints on r 0RR we initially make the simplest empirical assumption.…”
Section: The Clustering Strength Of Quasars and Radio Sourcesmentioning
confidence: 99%